2020
DOI: 10.1111/jch.14007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mass is the main somatic growth indicator associated with increasing blood pressure with age in children and adolescents

Abstract: Studies have shown that lean mass must be an important determinant of blood pressure value in children and adolescents. The absence of adjustment for the collinearity between lean and fat mass (FM), restricted age span, and lack of separate analysis by sex leave a gap in the literature. This study determined direct and indirect effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(30 reference statements)
1
4
1
Order By: Relevance
“…The results of this study show that children who did not crawl during infancy have higher levels of systolic and diastolic blood pressure at school age. This could be due to the association of SBP with levels of adipose and muscle tissue during childhood [37]. This observation is in line with previous studies showing that early infant locomotive development (lifting the body upwards to a standing position, walking with support and walking without support) was an early life predictor of adult blood pressure levels [38].…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study show that children who did not crawl during infancy have higher levels of systolic and diastolic blood pressure at school age. This could be due to the association of SBP with levels of adipose and muscle tissue during childhood [37]. This observation is in line with previous studies showing that early infant locomotive development (lifting the body upwards to a standing position, walking with support and walking without support) was an early life predictor of adult blood pressure levels [38].…”
Section: Discussionsupporting
confidence: 88%
“…measured the body composition of 201 boys and girls aged 6 to 17 years using a DXA scan and found that only fat-free mass was associated with SBP (7) . Similar results were reported by several other studies (2426) , although body composition in these studies was assessed by methodologies based on bioimpedance analysis which was thought less accurate than the gold standardised method (DXA scan) (27) . All these studies suggest that fat-free mass may play a dominant role in determining SBP in children and adolescents.…”
Section: Discussionsupporting
confidence: 84%
“…This is because approximately four out of ten of body composition is covered by skeletal muscle. Skeletal muscle blood supply represents about a quarter of the total resting cardiac output which indicates a higher metabolism rate than other tissues (Zaniqueli et al , 2020). Furthermore, skeletal muscle also act as main site of insulin action and secrete other muscle factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, skeletal muscle also act as main site of insulin action and secrete other muscle factors (e.g. adipokines) which possibly associate with development of hypertension (Gao et al , 2024; Zaniqueli et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation